The combined effects of salt feed, photoperiod, and temperature on Atlantic salmon smolt physiology, migratory behaviour, and sexual maturation - Lars Eirik Myklatun; Antony J. Prabhu Philip; Angelico Madaro; Audun Ø. Pedersen; Thomas W.K. Fraser; Trygve Sigholt; Tom J. Hansen; Birgitta Norberg; Sigurd Stefansson; Per Gunnar Fjelldal (Aquaculture, 2027)

Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

Reviewing the Severity of Handling‐Induced Injuries in the LAKSVEL Protocol for Salmon Welfare - Lars Helge Stien; Chris Noble; Angelico Madaro; Jonatan Nilsson; René Alvestad; Kristine Gismervik; Ewa Harasimczuk; Hogne Bleie; Karoline Skaar Amthor; Marc B. M. Bracke (Reviews in Aquaculture, 2025)
Injuries from lice treatments are ranked as a major cause of mortality and poor welfare for Atlantic salmon in marine net pens. As a result, scoring schemes based on the external appearance of injuries and severity are now frequently used. One such recently developed scheme for farmed salmon is the LAKSVEL protocol, inspired by previous schemes such as the SWIM models and the FISHWELL scoring system. Here we review the injury‐based welfare indicators (WIs) in the LAKSVEL protocol that can be associated with and induced by handling: Scale loss, Skin bleeding, Body wounds, Snout wounds, Eye injuries, Operculum damage, Gill status, and Fin damage. We used semantic modeling as a formalized procedure to attain information from the literature on how each of these injury‐based WIs is likely to affect the injured fish in the days and weeks to come. Based on the reviews, we then followed the semantic modeling procedure to define weighting categories and score the welfare consequences of each WI and their levels. Results showed that injuries to eyes, gills, and snout are particularly harmful to the fish, followed by penetrating body wounds, operculum damage, and fin damage; but also injuries such as scale loss and skin bleeding can have severe consequences, especially if they indicate unseen internal injuries. It is our hope that the presented reviews and modeling of welfare consequences will be a valuable resource for fish farmers and fish health personnel in their decision‐making processes and thereby contribute to improved fish welfare in the salmon aquaculture industry.

A Review on the Effects of the Doubled Maternal Genome in Triploids With a Suggested Pathway to Improving Their Performance in Aquaculture by Purging Deleterious Genes - Tom J. Hansen; Alison C. Harvey; Angelico Madaro; Aurélien Delaval; Kevin A. Glover; Monica F. Solberg; Thomas W. K. Fraser; Per Gunnar Fjelldal (Reviews in Aquaculture, 2025)
Triploid fish are usually sterile, a trait which reduces unwanted sexual maturation in fish farming and eliminates the risk for negative genetic effects of escapees on wild stocks. The triploid state, normally established through a doubling of the maternal genome, consists of two chromosome sets from the mother and one from the father. The increase in genome size is accompanied by an increase in cell volume and reduction in cell number that are associated with physiological effects which have been described in several studies. The doubled maternal genome is also mirrored in the triploid phenotype whereby meristic characters, growth, and physiology, are commonly biased towards that of the dam. However, chromosome doubling techniques are also known to give strong inbreeding effects. In meiotic gynogenes, this is seen in fitness‐related traits such as reduced survival, especially during early life, an increase in deformities, and lower growth. The same effects on fitness, although to a milder degree, are seen in triploids, which supports the hypothesis that they are also affected by inbreeding. Producing triploids by interploidy alleviate the inbreeding problem as the tetraploids can be crossbred to increase their heterozygosity. However, producing tetraploid broodstocks is both challenging and time and resource demanding. An alternative approach is to establish a triploid founder broodstock through one generation of gynogenesis. The gynogenesis will eliminate the lethal alleles, and by selecting the best performing individuals from the best performing families, one will also partially eliminate recessive deleterious alleles, increasing the fitness of the resulting triploid population.